Generalized Trapezoidal Fuzzy Soft Set and Its Application in Medical Diagnosis - Haidong Zhang; Lan Shu; Shilong Liao (Journal of Applied Mathematics)
Soft set theory is a newly emerging mathematical tool to deal with uncertain problems. In this paper, by introducing a generalization parameter, which itself is trapezoidal fuzzy, we define generalized trapezoidal fuzzy soft sets and then study some of their properties. Finally, applications of generalized trapezoidal fuzzy soft sets in a decision making problem and medical diagnosis problem are shown.